Identification and expression of the AREB/ABF/ABI5 subfamily genes in chickpea and lentil reveal major players involved in ABA-mediated defense response to drought stress - Marcos Fernando Basso; Paolo Iovieno; Maurizio Capuana; Felice Contaldi; Francesca Ieri; Felicia Menicucci; Fabrizio Lo Celso; Giampaolo Barone; Federico Martinelli (Planta, 2025)

Epigenetic changes induced by chronic and acute chromium stress treatments in Arabidopsis thaliana identified by the MSAP-Seq - Francesco Guarino; Angela Cicatelli; Werther Guidi Nissim; Ilaria Colzi; Cristina Gonnelli; Marcos Fernando Basso; Chiara Vergata; Felice Contaldi; Federico Martinelli; Stefano Castiglione (Chemosphere, 2024)

Identification and expression profile of the SMAX/SMXL family genes in chickpea and lentil provide important players of biotechnological interest involved in plant branching - Marcos Fernando Basso; Felice Contaldi; Fabrizio Lo Celso; César Milton Baratto; Maria Fatima Grossi-de-Sa; Giampaolo Barone; Antonio Ferrante; Federico Martinelli (Planta, 2024)
Main conclusion SMAX/SMXL family genes were successfully identified and characterized in the chickpea and lentil and gene expression data revealed several genes associated with the modulation of plant branching and powerful targets for use in transgenesis and genome editing. Abstract Strigolactones (SL) play essential roles in plant growth, rooting, development, and branching, and are associated with plant resilience to abiotic and biotic stress conditions. Likewise, karrikins (KAR) are “plant smoke-derived molecules” that act in a hormonal signaling pathway similar to SL playing an important role in seed germination and hairy root elongation. The SMAX/SMXL family genes are part of these two signaling pathways, in addition to some of these members acting in a still little known SL- and KAR-independent signaling pathway. To date, the identification and functional characterization of the SMAX/SMXL family genes has not been performed in the chickpea and lentil. In this study, nine SMAX/SMXL genes were systematically identified and characterized in the chickpea and lentil, and their expression profiles were explored under different unstressless or different stress conditions. After a comprehensive in silico characterization of the genes, promoters, proteins, and protein-protein interaction network, the expression profile for each gene was determined using a meta-analysis from the RNAseq datasets and complemented with real-time PCR analysis. The expression profiles of the SMAX/SMXL family genes were very dynamic in different chickpea and lentil organs, with some genes assuming a tissue-specific expression pattern. In addition, these genes were significantly modulated by different stress conditions, indicating that SMAX/SMXL genes, although working in three distinct signaling pathways, can act to modulate plant resilience. Most CaSMAX/SMXL and partner genes such as CaTiE1 and CaLAP1 , have a positive correlation with the plant branching level, while most LcSMAX/SMXL genes were less correlated with the plant branching level. The SMXL6 , SMXL7 , SMXL8 , TiE1 , LAP1 , BES1 , and BRC1 genes were highlighted as powerful targets for use in transgenesis and genome editing aiming to develop chickpea and lentil cultivars with improved architecture. Therefore, this study presented a detailed characterization of the SMAX/SMXL genes in the chickpea and lentil, and provided new insights for further studies focused on each SMAX/SMXL gene.

Expression profile of the NCED/CCD genes in chickpea and lentil during abiotic stress reveals a positive correlation with increased plant tolerance - Marcos Fernando Basso; Felice Contaldi; Fabrizio Lo Celso; Erna Karalija; Lenin Celiano Paz-Carrasco; Giampaolo Barone; Antonio Ferrante; Federico Martinelli (Plant Science, 2023)